Maternal and Cord Blood Folate Concentrations Are Inversely Associated with Fetal DNA Hydroxymethylation, but Not DNA Methylation, in a Cohort of Pregnant Canadian Women. Issue 2 (27th September 2019) - Plumptre, Lesley; Tammen, Stephanie A; Sohn, Kyoung-Jin; Masih, Shannon P; Visentin, Carly E; Aufreiter, Susanne; Malysheva, Olga; Schroder, Theresa H; Ly, Anna; Berger, Howard; Croxford, Ruth; Lamers, Yvonne; et al.
ABSTRACT: Background: Aberrancies in fetal DNA methylation programming may modify disease susceptibility of the offspring. Maternal folate status has potential to alter fetal DNA methylation. Objectives: We examined the association of maternal and cord blood concentrations of folate and unmetabolized folic acid (UMFA), vitamin B-12, vitamin B-6, and choline with fetal DNA methylation and hydroxymethylation and assessed potential modifying effects of 38 fetal genetic variants in 22 genes. Methods: Nutrient blood concentrations were measured in 368 pregnant women in early pregnancy (12–16 wk of gestation) and at delivery (37–42 wk of gestation) and in cord blood. DNA methylation and hydroxymethylation in cord blood mononuclear cells were quantified by LC-MS/MS. Pearson partial correlations were used to determine the association between individual nutrients and DNA methylation and hydroxymethylation. Results: Serum and RBC folate and plasma UMFA concentrations (primary outcomes) in early pregnancy, at delivery, and in cord blood were not significantly associated with fetal DNA methylation. In contrast, maternal RBC folate in early pregnancy ( r  = −0.16, P  = 0.04) and cord plasma UMFA ( r  = −0.23, P  = 0.004) were inversely correlated with fetal DNA hydroxymethylation. Neither maternal and cord blood concentrations of other nutrients nor fetal genotypes (secondary outcomes) were significantly associated with fetal DNA methylation or hydroxymethylation. Infants born to mothers with RBC folate concentrations in the highest quartile and serum vitamin B-12 concentrations in the lowest quartile in early pregnancy had significantly lower fetal DNA methylation and higher birth weight compared with those born to mothers with lower RBC folate and higher serum vitamin B-12 concentrations ( P  = 0.01). Conclusions: Maternal and cord blood folate concentrations are associated with fetal DNA hydroxymethylation, but not DNA methylation, in a cohort of pregnant Canadian women. The observation that high folate and low vitamin B-12 maternal status in early pregnancy may be associated with decreased fetal DNA methylation and higher birth weight warrants further investigation. This trial was registered at clinicaltrials.gov as NCT02244684.